PERLINDUNGAN KONSUMEN ATAS KLAIM BERLEBIH PRODUK KOSMETIKA DALAM PERIKLANAN SECARA ENDORSEMENT - Mahayuni, Ni Putu Gita; Putra, Made Aditya Pramana (Kertha Negara : Journal Ilmu Hukum, 2024)
This article was made purpose to aims in terms of the consumer protection regulation from endorsement content of cosmetic product in Indonesia and legal sanctions given for business people that are detrimental to consumers from overclaim in endorsement content of cosmetic product. Study uses normative legal research methods through approaches in legislation and fact approaches and uses primary legal materials and secondary legal materials. The resultsof this study indicate that regulation in Indonesia have been regulated about prohibition to enter overclaim of cosmetic product in advertising in Indonesia, however there is void of norm because the regulation about endorsement have not regulated explicitly. Business people can be worn administrative sanction and criminal sanction as regulated in Law Nomor 8 1999 Customer Protection and Regulation of The Indonesian Food and Drug Authority Nomor Nomor 3 2022 Technical Rewuirements for Cosmetic Claims when consumer get disadvantage from overclaim in endorsement advertising.